2013
DOI: 10.1515/cog-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Language statistics and individual differences in processing primary metaphors

Abstract: Research in cognitive linguistics has emphasized the role of embodi ment in metaphor comprehension, with experimental research showing acti vation of perceptual simulations when processing metaphors. Recent research in conceptual processing has demonstrated that findings attributed to em bodied cognition can be explained through language statistics. The current study in vestigates whether language statistics explain processing of primary metaphors and whether this effect is modified by the gender of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The findings presented here are in line with what we have claimed for first-order (Hutchinson & Louwerse, 2013 ) and higher-order (Recchia & Louwerse, 2015 ) co-occurrences. Language users translate prelinguistic conceptual knowledge into linguistic conceptualizations, so that as a function of language use, language statistical patterns are encoded in language (Louwerse, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings presented here are in line with what we have claimed for first-order (Hutchinson & Louwerse, 2013 ) and higher-order (Recchia & Louwerse, 2015 ) co-occurrences. Language users translate prelinguistic conceptual knowledge into linguistic conceptualizations, so that as a function of language use, language statistical patterns are encoded in language (Louwerse, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…The effect sizes may seem small and therefore these findings may seem negligible. However, let us assume the general linguistic context of a word can predict the valence of a word (Recchia & Louwerse, 2015 ) and so can the immediately preceding words (Hutchinson & Louwerse, 2013 ). The current study has shown that nasals in the first position of the word predict the valence only with approximately 55% accuracy (Event A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Conceptual Metaphor Theory account hypothesizes that LMs are an outgrowth of metaphorical thought, which is in turn an outgrowth of embodied experiences that conflate source and target domains-experience structures thought, and thought structures language (Lakoff, 1993). However, recent critics have argued for the opposite causal direction: Linguistic regularities may drive the mental mapping between source and target domains (Hutchinson and Louwerse, 2013;Casasanto, 2014;Hutchinson and Louwerse, 2014). Our results show that, at least for AN pairs, the semantic structure of a source domain and its mapping to a metaphorical target domain are available in the distributional statistics of language itself.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of previous work on metaphor is that, with the exception of a small number of papers, few attempts have been made to investigate the extent to which the reaction time behavior reflects distributions within language corpora. One exception to this is Hutchinson and Louwerse's (2013) study in which they compared the ways in which male and female participants responded to primary metaphors in a reaction time study. They showed that vertical associations in line with the HAPPY IS UP metaphor were more driven by corpus-based frequency differences (e.g., how often 'happy-sad' was mentioned as opposed to 'sad-happy') for women than for men.…”
Section: Introductionmentioning
confidence: 99%